Paroxysmal nocturnal hemoglobinuria masquerading as hemolytic uremic syndrome: a Case Report - Menghan Gao; Bo Liu; Jianping Yao; Fuhan Huang (Frontiers in Medicine)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired disorder of intravascular hemolysis caused by a somatic mutation in the gene responsible for glycosylphosphatidylinositol (GPI)-anchored complement regulatory proteins. This mutation leads to the production of abnormal blood cell clones lacking CD55 and CD59. PNH can result in renal damage. The challenge of early identification and diagnosis leads to misdiagnosis as other intravascular hemolytic conditions. This paper presents a case that began with fever, diarrhea, and acute renal failure, initially misdiagnosed as atypical hemolytic uremic syndrome (aHUS) but later confirmed as PNH through renal biopsy and related diagnostic tests. After treatment, the patient’s renal function recovered, and anemia improved. Intravascular hemolysis is a prominent feature common to both PNH and HUS. They exhibit similar clinical manifestations, which pose a challenge for differential diagnosis. Unlike previous reports, the patient in this case denied any history of hematologic disorders, which made the diagnosis more challenging.